Supply Chain of Subsidized Chemical Fertilizers in Nepal - Panta, H. K. (Journal of the Institute of Agriculture and Animal Science, 2018)
A survey was conducted with different supply chain actors of chemical fertilizers for studying the supply chain of chemical fertilizers in Nepal in 2018. Chemical fertilizers in Nepal are imported from different manufacturing countries like Turkey, China, Egypt and India by global tender and by government to government negotiation especially from India. Potential demand for fertilizer in Nepal is about 7,00,000 MT of which actual supply in the year 2016/17 was 3,24,977MT. Average subsidy on chemical fertilizer in Nepal since 2008/09 is estimated to be NRs. 3,73,42,27,780 (43.78%). Procurement, shipping, warehousing at port, inland transportation, inland warehousing, local transportation, distribution and consumption are major supply chain functions of chemical fertilizer specific to Nepal. Final sell price of urea, DAP and MOP in Sindhupalchhok in the year 2016 was found 37, 15 and 23% respectively higher than entry point sell price. Non-conducive policy environment, ineffective regulation, lack of fund and poor infrastructure are major problems of fertilizer supply in Nepal. Illegal trading from open border of India and selling of subsidized fertilizers by unauthorized agro-dealers are other problems of this sector.Though government has been investing large revenue in fertilizer subsidy, expected results in productivity enhancement has not been met. Assured supply of quality fertilizer in time is more important even than the price of fertilizer. Therefore, emphasis is to be led on implementation of conducive policy, strict regulation and infrastructure development focusing on timely supply, judicious application, checking illegal trading along with the promotion of use of organic manures.